Entre Jesus e Barrabás: realidade, expectativas e a escolha da multidão em Marcos 15,6-15 - Cuesta, Ruthe Ventura (2009)
The following work aims to present a study on the word crowd in the Mark s book, considering it is an important character on the literary structure conceived by the author, highlighting specially its performance on the scene of the presentation of Jesus before Pilate in which is given it the crowd the opportunity to choose the freedom of either Jesus or Barabbas. The referred text will be studied taking into consideration the context of roman overrule in which it was put in , as a literary composition that reproduces the structure of munera (a battle between gladiators), featured phenomenon of the roman civilization and symbol of their domination, making the writing of Mark to be a mockery which intends to enlighten its public concerning its own situation.(AU)